1979
DOI: 10.1021/ja00497a061
|View full text |Cite
|
Sign up to set email alerts
|

Anion complexes of ferrous porphyrins

Abstract: 13) This assumption is supported by the fact that the formatlon of Cl3~i s not affected (no decrease in the Cl3_ concentration) by adding a large amount of unreactive gas, argon, to thermalize at least partially the Cl-Ions.(14) Z. Karpas and F. S. Klein, Int. J. Mass Spectrom. Ion Phys.. 22, 189 (1976).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 1 publication
3
48
0
Order By: Relevance
“…The strong H-bond is believed to result in increased electron density on the histidine imidazole-Fe-porphyrin system, which would aid in stabilizing both the heme and radical electron-deficient centers that exist in compound ES. Several studies have been published that agree with this idea (Mincey & Traylor 1979;Traylor & Popovitz-Biro, 1988;Fujita et al, 1983). Strong proximal H-bonding might therefore be expected to be a general feature of the heme peroxidases in general.…”
mentioning
confidence: 65%
“…The strong H-bond is believed to result in increased electron density on the histidine imidazole-Fe-porphyrin system, which would aid in stabilizing both the heme and radical electron-deficient centers that exist in compound ES. Several studies have been published that agree with this idea (Mincey & Traylor 1979;Traylor & Popovitz-Biro, 1988;Fujita et al, 1983). Strong proximal H-bonding might therefore be expected to be a general feature of the heme peroxidases in general.…”
mentioning
confidence: 65%
“…Teraoka et al [215] have shown that a characteristic of peroxidases is an Fe-N stretching frequency for the iron(II)-proximal histidine linkage that occurs 20 cm À1 higher than the corresponding vibrations of hemoglobin or myoglobin. The high m Fe(II)-his frequencies found for peroxidases are attributed to partial imidazolate character of the proximal histidine, induced by a hydrogen bond between the proximal histidine and an aspartate residue [202,[216][217][218][219][220][221], which are His-170 and Asp-247 for HRP-C. The m Fe(II)-his frequencies exhibit characteristic pH-dependence [222][223][224] that correspond to heme-linked ionizations of the ferrous enzyme [174,225].…”
Section: Discussionmentioning
confidence: 99%
“…Large changes in wavelength would be expected if the iron-histidine bond were ruptured, since in model compound data it was reported that the Soret maximum shifts from -420 nm to -390 nm upon going from six to fivecoordination when the nitrogenous fifth ligand is lost (27). Similarly, when a weak field ligand, such as H20, occupies the fifth position in a CO-bound heme complex, the peak of the Soret transition is shifted substantially to shorter wavelengths as compared with complexes with imidazole at that position (28,29). We conclude that for CO-bound Mb at low pH, the heme is six-coordinate and the fifth ligand is histidine.…”
Section: Discussionmentioning
confidence: 99%